Mental wellbeing and engagement in health risk behaviours in German university students during the COVID-19 pandemic: Findings of a cross-sectional study. (20th October 2021) - Busse, H; Fialho, P M; Stock, C; Pischke, CR; Buck, C; Spatafora, F; Kühne, L; Zeeb, H; Wendt, C; Helmer, SM
Abstract: Background: Daily life of higher education students across the world changed profoundly in 2020 with the implementation of governmental and institutional measures to control the COVID-19 pandemic. We investigated mental wellbeing and engagement in health risk behaviours (HRB) in German university students at the start of the COVID-19 pandemic. Methods: Data stem from the COVID-19 International Student Wellbeing Study (C19 ISWS). The web-based survey was conducted in May 2020 at four German universities. HRBs included tobacco and cannabis use, alcohol consumption, and engagement in physical activity. All HRBs were assessed retrospectively and at the time of data collection. Mental wellbeing was assessed using the 8-item Center for Epidemiologic Studies-Depression Scale (CES-D 8). We conducted multinomial regression analyses to investigate factors associated with changes in HRBs and latent transition analysis to identify substance use profiles. Results: 5021 students completed the survey (69% female; mean age 24.4 years, SD = 5.1). The mean score for depressive symptoms was 9.25 (SD = 0.67, range 0-24). Sixty-one percent of students reported consuming alcohol, 46% binge drinking, 44% inactivity, 19% smoking and 11% cannabis use. While smoking and cannabis use remained unchanged during the COVID-19 pandemic, 24% reported a decrease in binge drinking. Changes to physical activity were frequently reported, with 31% reporting an increase and 19% reporting a decrease in vigorous physical activity. Higher depressive symptoms were found to be associated with changes in HRBs. Five substance use behaviour profiles were identified, which remained fairly unchanged. Conclusions: Engagement in HRBs remains at high level during the COVID-19 pandemic among German students. Depressive symptoms were found to be associated with changes in HRBs. Efforts to promote student health and wellbeing are needed in times of the COVID-19 pandemic and thereafter to prevent longer-term consequences.